Penerapan Standar Akuntansi Keuangan-Entitas Tanpa Akuntanbilitas Publik (SAK-ETAP) Pada PT. Mutiara Prima Sukses - Ashar Basyir (ARBITRASE: Journal of Economics and Accounting, 2022)
Application of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) is intended to be used by Entities Without Public Accountability (ETAP), entities in implementing which are carried out starting from; reporting, presentation, measurement and recognition in order to realize and produce a complete financial report. The objectives in this research are; know how reporting, presentation, measurement and recognition of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) at PT. Prima Pearls of Success. This study uses a descriptive qualitative approach. Data collection techniques through interviews and documentation. In analyzing data apply reporting, presentation, measurement and recognition based on Accounting Standards for Financial Entities Without Public Accountability (SAK-ETAP). Based on the research results, the company in general has implemented reporting, presentation, measurement and recognition based on the Accounting Standards for Financial Entities Without Public Accountability (SAK-ETAP), it's just that in the recognition of company account posts there are several account items that are not recorded and not presented in the company's financial reporting.